Determinants of Firm Profitability in Colombia's Manufacturing Sector : Exchange Rate or Structural? - Griffin, Naomi (Washington, D.C. : International Monetary Fund, 2015)
The appreciation of the real exchange rate over the past several years is considered one of the key drivers behind the weak performance of Colombia's manufacturing sector in recent years. This paper examines the effects of the real exchange rate, external and domestic demand, and structural changes on firms' profitability in Colombia's manufacturing sector between 2000 and 2012. While export intensive companies have suffered lower profit growth with real exchange rate appreciation,we find no strong evidence that real appreciation has, on average, negatively affected the profitability of manufacturing firms; on the contrary, we find that real appreciation may have increased firms' profitability by reducing the cost of imported inputs as Colombian manufacturing firms become more domestically oriented. At the same time, some structural changes (related to trade disruption with Venezuela and increased trade competition from China) seem to partially explain the weakness of the manufacturing sector since 2008.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet